Lateral cephalometric values of FKG ULM students Banjar ethnic according to Steiner analysis - Sandria Aprilano; Diana Wibowo; Norlaila Sarifah (Jurnal Radiologi Dentomaksilofasial Indonesia (JRDI), 2022)
Objectives: This study aimed to determine the value of dentocraniofacial measurements of FKG ULM students from Banjar ethnic in terms of lateral cephalometric radiography using Steiner analysis. Materials and Methods: Cephalometric measurements were performed using the Steiner analysis method on skeletal landmarks: SNA, SNB and ANB; dental: UI-NA, LI-NB, and interincisal angle. Data analysis was performed by descriptive statistical method. Results: The average skeletal and dental value of the FKG ULM students from Banjar ethnic at the SNA angle is 86.31°± 4.49°, the SNB is 81.33°± 4.39°, the ANB is 4.98°± 2.05°, the UI-NA angle is 19.69°± 8.22°, the LI-NB angle is 28.65°± 6.76°, the UI-NA distance is 4.45± 2.86 mm, the LI-NB distance is 8.58± 3.19 mm and the interincisal angle is 126.43°± 10.51°. Conclusion: The dental and skeletal averages showed that the FKG ULM students from Banjar ethnic had more prognathic maxillary and mandibular positions and more protrusive maxillary and mandibular incisor positions than the normal standard of Steiner's analysis.